Execution and pauses in writing narratives: processing time, cognitive effort and typing skill - Rui Alexandre Alves (2008)
At the behavioural level, the activity of a writer can be described as periods of typing separated by pauses. Although some studies have been concerned with the functions of pauses, few have investigated motor execution periods. Precise estimates of the distribution of writing processes, and their cognitive demands, across periods of typing and pauses are lacking. Furthermore, it is uncertain how typing skill affects these aspects of writing. We addressed these issues, selecting writers of low and high typing skill who performed dictation and composition tasks. The occurrences of writing processes were assessed through directed verbalization, and their cognitive demands were measured through interference in reaction times (IRT). Before writing a narrative, 34 undergraduates learned to categorize examples of introspective thoughts as different types of activities related to writing (planning, translating, or revising). Then, while writing, they responded to random auditory probes, and reported their ongoing activity according to the learned categories. Convergent with previous findings, translating was most often reported, and revising and planning had fewer occurrences. Translating was mostly activated during motor execution, whereas revising and planning were mainly activated during pauses. However, none of the writing processes can be characterized as being typical of pauses, since translating was activated to a similar extent as the other two processes. Regarding cognitive demands, revising is likely to be the most demanding process in narrative writing. Typing skill had an impact on IRTs of motor execution. The demands of execution were greater in the low than in the high typing skill group, but these greater demands did not affect the strategy of writing processes activation. Nevertheless, low typing skill had a detrimental impact on text quality.